Ecophysiological Response of Vitis vinifera L. in an Urban Agrosystem: Preliminary Assessment of Genetic Variability - Elena Brunori; Alessandra Bernardini; Federico Valerio Moresi; Fabio Attorre; Rita Biasi (Plants, 2022)
Urban agriculture is an emerging challenge. Identifying suitable agrosystems that allow for the multiple functions of urban agriculture represents a key issue for the reinforcement of the agricultural matrix in cities, with the aims of counteracting and adapting to climate change and providing economic and social benefits. This study aims to produce a preliminary assessment of the adaptability of Italian native and non-native Vitis vinifera L. cultivars to the stressors of an urban environment. The investigation was carried out on the grapevine collection of the Botanical Garden of Rome (“Vigneto Italia”). A total of 15 grapevine varieties were selected for the evaluation of leaf chlorophyll content, stomatal conductance, and chlorophyll fluorescence under abiotic conditions during the growing season of 2021. Spectral signatures were collected from mature leaves, and several vegetation indices (LWI, MCARI, and WBI) were calculated. Our preliminary results highlighted differences in the behavior of the grapevine cultivars. The native ones showed a medium-high level for leaf chlorophyll content (greater than 350 mol m−2), good photosynthetic efficiency (QY > 0.75), and optimal stomatal behavior under drought stress (200 > gs > 50 mmol H2O m−2 s−1). The data allowed for the classification of the tested genotypes based on their site-specific resistance and resilience to urban environmental conditions. The grapevine proved to be a biological system that is highly sensitive to climate variables, yet highly adaptable to limiting growing factors.